A long-term mouse testis organ culture system to identify germ cell damage induced by chemotherapy - Satoshi Yokota; Kiyoshi Hashimoto; Takuya Sato; Koichi Uemura; Kazuhide Makiyama; Takuya Nishimura; Satoshi Kitajima; Takehiko Ogawa (Current Research in Toxicology)
We previously developed the acrosin-green fluorescent protein (GFP) transgenic neonatal mouse organ culture system for rapid and accurate assessment of testicular toxicity. This system effectively evaluates drug-induced toxicity in male germ cells before meiotic entry but cannot assess post-meiotic germ cell toxicity. For many chemicals, the specific stage of germ cell differentiation that is susceptible to toxicity remains unclear, highlighting the need for new methods. In this study, we incubated neonatal mouse testis organ cultures for 35 days to allow post-meiotic cells to develop. The tissue was then exposed to cisplatin to determine the cells that are targeted and to assess the reversibility of the toxicity. We monitored changes in tissue volume and GFP fluorescence, which tracks the progression of spermatogenesis, and confirmed findings by histological analysis. Cisplatin inhibited tissue growth and reduced GFP fluorescence in a concentration-dependent manner. Higher concentrations targeted not only spermatogonia, but also spermatocytes and spermatids. Recovery from toxicity was observed at clinically relevant doses. This study demonstrates that long-term mouse testis organ culture can be used to assess testicular toxicity, enabling the identification of specific germ cell stages targeted by chemicals such as cisplatin.